A Comprehensive Analysis Of Startup Ecology In India With Reference To Young Entrepreneurs In Digital Era - Chandra Bhooshan Singh; Rakshak Bharti; Satvik Jain (Involvement International Journal of Business, 2024)
This study explores the complex dynamics of India's startup scene with a particular emphasis on the critical role that young entrepreneurs play in the wake of the digital revolution. In light of India's significant economic transition to a technology-driven economy, this study attempts to offer a comprehensive overview of the opportunities, obstacles, and cutting-edge strategies that are emerging in the startup scene. Through an analysis of past viewpoints, present patterns, and potential future developments, the article illuminates the development of the ecosystem and highlights the adaptability and ingenuity of youthful entrepreneurs utilising digital technologies. This investigation adds to the continuing conversation on creating an atmosphere that is favourable for startups to prosper in India, with a particular emphasis on government regulations, frameworks, and case studies of prosperous endeavours. The abstract lays the groundwork for a thorough examination, emphasising the role that young creativity and the digital environment play in determining the course of the Indian startup ecosystem.